2016
DOI: 10.1108/ijcst-11-2014-0132
|View full text |Cite
|
Sign up to set email alerts
|

The research on surface non-uniformity of textile systems

Abstract: Purpose -The purpose of this paper is to investigate the non-uniformity of the surface where textile fabric systems were joined using embroidery with the help of the system dimensional scanning. Design/methodology/approach -To ascertain and evaluate surface non-uniformity and puckering of the embroidered elements dimensional 3D laser scanner was used. The dimensional 3D model of the embroidered element was imported into the software package RapidformTM and returned to the beginning of the coordinate system for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…[13][14][15] The mechanical properties of the fabric, such as the warp seam pucker of the thin silk fabrics decrease as the tensile modulus of the fabric increases, 16 the seam pucker of cotton fabrics increases with decreasing shear stiffness, 17 the seam pucker of fabric with smaller bending stiffness becomes more obvious. 18,19 Other studies have shown that sewing process parameters are also the most direct factor affecting the degree of seam pucker, for example, the composition, shrinkage rate and elongation of the sewing thread will also affect the seam pucker, 20,21 the pressure of the presser foot is higher than the critical buckling load of the fabric, and it is easy to cause seam pucker, 22 as the needle size increases, the seam pucker also increases. 23 Kim et al 24 observed that seam pucker was most strongly affected by the stitch length, cotton and polyester fabrics reduce seam pucker as stitch density decreases, 25 the pressure of the main shaft of the sewing machine is reduced, the rotation frequency is increased, and the seam pucker is increased.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The mechanical properties of the fabric, such as the warp seam pucker of the thin silk fabrics decrease as the tensile modulus of the fabric increases, 16 the seam pucker of cotton fabrics increases with decreasing shear stiffness, 17 the seam pucker of fabric with smaller bending stiffness becomes more obvious. 18,19 Other studies have shown that sewing process parameters are also the most direct factor affecting the degree of seam pucker, for example, the composition, shrinkage rate and elongation of the sewing thread will also affect the seam pucker, 20,21 the pressure of the presser foot is higher than the critical buckling load of the fabric, and it is easy to cause seam pucker, 22 as the needle size increases, the seam pucker also increases. 23 Kim et al 24 observed that seam pucker was most strongly affected by the stitch length, cotton and polyester fabrics reduce seam pucker as stitch density decreases, 25 the pressure of the main shaft of the sewing machine is reduced, the rotation frequency is increased, and the seam pucker is increased.…”
Section: Introductionmentioning
confidence: 99%